Quality systems and practices in agro-ecotourism enterprises in rural trans-border regions - Electra Pitoska (European Regional Science Association (ERSA), 2012)
Tourism comprises a self- contained phenomenon synonymous to consumption and spare time and its growth, due to the development of technology and the improvement of the standards of living, has taken global dimensions. As a result tourism has developed to a pure industry, leading the economy and society in local, regional, national and global level to important changes. Based to the quality and the value of the natural and cultural heritage, as well as to the growth of the level of the given services, tourism is directed to the boom of alternative types of tourism and especially agro-ecotourism, which went through an enormous rise and demand. The change of the consumer's behavior and the tourist's consideration of the environment has led organizations taking actions in the sector, to the adoption of high level of standards in all aspects of the generative procedure. The main reason for this continual improvement of the service level and the quality of the given services, as well as the clamp-down for the protection of the environment, was the reason that sustainable tourist growth became a stratigical aim. The quality and the practices that ensure sustainability are a continuous procedure which is accomplished with the implementation of quality systems, aiming to achieve the Total Quality. Companies with comply with the specific standards receive quality marks, which conform to this kind of favour that will remain to the consumer's consciousness. In that perspective, the aim of the research was to examine whether agro-ecotourist enterprises are certified for the given services, for the protection for the consumers/ tourists, as well as for the protection of the environment. The research was carried out in the last four months of 2011 in three regions which are to three deferent countries. The regions are in the Trans- border area in Northern Greece, South Albania and South F.Y.R.O. Macedonia. Through the use of questionnaires and personal interviews, data was gathered and analyzed with the use of SPSS. Through statistical analysis, we detect that the majority of the organizations do not apply any certification system for the services that offer. However, most of the entrepreneurs were disposed to learn them and apply them to their companies.
Keywords: R10; R11; 330; Tourism enterprises; quality systems; consumer's protection; Trans border areas